Physicochemical characterization and biological evaluation of amorphous solid dispersions of an anticancerous drug: Erlotinib HCl - K. P. Safna Hussan; Thekkekara D. Babu; M. Shahin Thayyil; T. S. Sreeshma; A. Archana (Scientific Reports)
Abstract Erlotinib hydrochloride (ERL), a tyrosine kinase inhibitor, is effective in treating various cancers. However, low aqueous solubility limits its bioavailability and therapeutic efficacy. We developed an amorphous solid dispersion (ASD) of ERL with biocompatible polymers, polyvinylpyrrolidone (PVP-K30), and polyethylene glycol (PEG-4000) for enhanced amorphization, miscibility, and molecular interactions. The present study focuses on the physicochemical characterization of formulated ASD of ERL using Fourier Transform Infrared Spectroscopy (FTIR), X-ray Powder Diffraction (PXRD), UV–Visible Spectroscopy, and High-Performance Liquid Chromatography (HPLC), along with biological evaluation including antioxidant, cytotoxicity, and antitumor studies in mouse tumor models. FTIR analysis confirmed the retention of ERL’s characteristic peaks in ASDs with PVP, PEG, and PVP/PEG, with shifts to lower frequencies for C=O bending, CH₂ deformation and CH symmetric deformation, indicating reduced molecular vibration energy, increased molecular flexibility, and strong drug–polymer interactions. PXRD analysis confirmed the transformation of crystalline ERL into an amorphous state in ASDs, as evidenced by the diminished ERL peaks at 11.7°, 16.2°, 21.7°, 24.75°, 25.56°, and 29.37°. UV spectroscopy revealed shifts in absorption peaks (256 nm), suggesting favorable drug–polymer interactions. HPLC demonstrated enhanced release rates at 4.72 retention time. In dissolution studies, the ERL + PEG formulation attained the greatest dissolution rate (80%). ERL + PVP showed superior DPPH radical scavenging activity with an IC50 value of 100 µg/mL, while ERL + PEG demonstrated stronger hydroxyl radical scavenging activity with an IC50 of 200 µg/mL. In the MTT assay, ERL + PEG exhibited the most potent cytotoxicity against MCF-7 cells, with an IC50 of 19 μM, whereas the ERL + PEG + PVP combination was most effective against HCT-116 cells, with IC50 of 19.5 μM. In vivo, ERL + PEG significantly reduced tumor volumes to 0.167 ± 0.002 g and 0.063 ± 0.004 g, corresponding to a tumor reduction of 98.78%. This study highlights the successful development of erlotinib ASD, particularly with PEG, which significantly improved ERL’s solubility, dissolution rate, antioxidant activity, cytotoxicity, and antitumor efficacy. These enhancements are attributed to physical modifications such as enhanced amorphization and strong drug–polymer interactions, without any chemical alteration of ERL, underscoring the potential of this formulation as an effective and promising drug delivery strategy for cancer therapy.